Macroflora as a Bio-Trap for Airbone Particulate Matter - Abdul Haqi, Ibrahim; Nor Azam, Ramli; Ayu Wazira, Azhari; Norazian, Mohamed Noor (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.